Optimalisasi Sumber Daya Manusia dan Manajemen Waktu untuk Pemberdayaan E-Commerce di Desa Tanjung Laut - Muhammad Taufik Hidayat; Fitriasuri Fitriasuri; Bakti Setyadi; Poppy Indriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Tanjung Laut Village holds significant potential in the songket handicraft sector. However, local artisans face challenges in utilizing digital technology for marketing. This community engagement project aims to optimize human resources and time management to support the adoption of e-commerce among local MSMEs. The methods include time management training, e-commerce workshops, international HR management socialization, and Focus Group Discussions (FGDs). The results show an increased understanding of digital marketing strategies and production time planning. These trainings also encouraged collaboration and technology adoption, expected to enhance the village’s economic independence and competitiveness.